Macroprudential banking regulation: Does one size fit all? - Doris Neuberger; Roger Rissi (Universität Rostock, Institut für Volkswirtschaftslehre, 2012)
The macroprudential regulatory framework of Basel III imposes the same capital and liquidity requirements on all banks around the world to ensure global competitiveness of banks. Using an agent-based model of the financial system, we find that this is not a robust framework to achieve (inter)national financial stability, because efficient regulation has to embrace the economic structure and behaviour of financial market participants, which differ from country to country. Market-based financial systems do not profit from capital and liquidity regulations, but from a ban on proprietary trading (Volcker rule). In homogeneous or bank-based financial systems, the most effective regulatory policy to ensure financial stability depends on the stability measure used. Irrespective of financial system architecture, direct restrictions of banks' investment portfolios are more effective than indirect restrictions through capital, leverage and liquidity regulations.
Keywords: C63; G01; G11; G21; G28; 330; financial stability; systemic risk; financial system; banking regulation; agent-based model; Bankenaufsicht; Basler Akkord; Internationales Finanzsystem; Agentenbasierte Modellierung; Finanzkrise; Systemrisiko; Theorie; Welt